Devolution of HRM practices : Perspectives of two major Japanese electrical and electronics companies in Malaysia - Abang Ekhsan, Abang Othman (Canadian International Council (CIC), 2008)
Purpose - This study examines the devolution of HRM functions, the rationale and problems of such devolution to line management in the context of applications and processes in two major Japanese multinational companies in Malaysia.